Reliability of the MS-2 system in detecting methicillin-resistant Staphylococcus aureus. - Boyce, J M (1982)
The MS-2 system (Abbott Diagnostics, Division of Abbott Laboratories, Dallas, Tex.) is an automated system capable of rapid antimicrobial susceptibility testing. However, the short incubation periods used by the device may adversely affect its ability to detect slowly growing resistant organisms. Shortly after the introduction of the MS-2 system into the University of Mississippi Medical Center clinical microbiology laboratory, we noted discrepancies between the MS-2 and the disk diffusion susceptibility reports when methicillin-resistant Staphylococcus aureus isolates were tested. Subsequently, we determined the susceptibilities of 75 such isolates by the MS-2 and Kirby-Bauer disk diffusion methods and measured the minimum inhibitory concentrations of methicillin, oxacillin, and cephalothin for 33 of the 75 isolates by standardized agar dilution techniques. There was only 47% overall agreement between the MS-2 and disk diffusion methods when methicillin was tested and 15% agreement when cephalothin was the test drug. There was 93% or more overall agreement between the two methods when other antimicrobial agents were tested. The minimum inhibitory concentration of methicillin was greater than or equal to 16 micrograms/ml for all 33 isolates evaluated by the agar dilution method. A comparison of the MS-2 and agar dilution results revealed an overall agreement of 49% when the susceptibilities to methicillin were determined. The MS-2 system reported that multiple methicillin-resistant S. aureus isolates obtained from a single patient were either resistant, intermediate, or sensitive to methicillin. Inconsistent results were also obtained when a single isolate was tested simultaneously in 10 cuvette cartridges. We conclude that the MS-2 system does not reliably detect methicillin and cephalothin resistance among S. aureus.